Attitudinal Choquet integrals and applications in decision making. Issue 4 (6th February 2018) - Aggarwal, Manish
Abstract: The compensation capabilities of Choquet integral are augmented to consider the complex attitudinal character of a decision maker. The resulting operator is termed as attitudinal Choquet integral (ACI). The proposed ACI is further extended as induced ACI. The special cases of ACI are investigated. The usefulness of ACI is shown through a case study.